(untitled) (Web of Teachers: Inderscience Research, 2024)
The article deals with the application of creative methods and approaches in the process of teaching Russian literature. The author presents an analysis of the effectiveness of such methods, as well as their impact on the level of students’ understanding and interest in Russian literature. The study includes key techniques and examples of successful results, as well as suggestions for further improvement of the teaching process.